2019
DOI: 10.1159/000499573
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Retrograde Semirigid and Flexible Ureteroscopic Lithotripsy for the Treatment of Large Ureteral Stones Equal of or Greater than 15 mm? Results from a Single Center

Abstract: Purpose: To present the results and complications of retrograde ureteroscopic lithotripsy for treatment of large ureteral stones. Methods: Nineteen patients were treated for ureteral stones ≥15 mm detected in CT or plain KUB film. Endoscopy was performed with either a semirigid or flexible ureteroscope. Stone fragmentation was performed using a 30 W Holmium laser. Results: The mean stone size was 20.7 mm (range 15–30). The mean duration of the operation was 82 min (45–140). Measures to prevent retropulsion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…16 Kozyrakis et al used semirigid URS combined with flexible URS in large upper ureter stone treatment. 17 In our study, the stone-free rate was 72.6% after the first procedure, and the final stone-free rate was 95.2% following additional intervention. Although we have demonstrated that upper ureteral and renal pelvis stones could be successfully treated with semirigid URS, we think that it cannot essentially replace the flexible URS procedure, especially when it comes to the renal pelvis stone treatment issue.…”
Section: Discussionsupporting
confidence: 44%
“…16 Kozyrakis et al used semirigid URS combined with flexible URS in large upper ureter stone treatment. 17 In our study, the stone-free rate was 72.6% after the first procedure, and the final stone-free rate was 95.2% following additional intervention. Although we have demonstrated that upper ureteral and renal pelvis stones could be successfully treated with semirigid URS, we think that it cannot essentially replace the flexible URS procedure, especially when it comes to the renal pelvis stone treatment issue.…”
Section: Discussionsupporting
confidence: 44%
“…They reported that,these patients then underwent retrograde endoscopic lithotripsy, which completely cleared the calculi in one session with any complication. In another recent study, Kozyrakis et al reported the effectiveness of retrograde semirigid and flexible ureteroscopic lithotripsy for the treatment of large ureteral stones equal of or greater than 15 mm in 19 patients (21). According to their study, a subsequent RIRS during the same session was necessary in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…As a new type of lithotomy in recent years, ShuoTong ureteroscopy is performed with holmium laser lithotripsy through the standard scope and ureteral passage and combined with scabbard in the body. Then the controlled pressure system was used to suction residual lithotripsy to ensure the normal function of the kidney and ureter system, and the residual stone rate was low (7,8). There are limited samples of ultra-mini percutaneous nephrolithotripsy and macroscopical treatment in foreign countries, and there are few studies on polycystic kidney combined with renal stones (9).…”
Section: Introductionmentioning
confidence: 99%